Human Plasmodium knowlesi infections in South-East Asian countries - Myo Thura Zaw; Zaw Lin (Elsevier Taiwan LLC, 2019)
Plasmodium knowlesi is now regarded as the fifth malaria parasite causing human malaria as it is widely distributed in South-East Asian countries especially east Malaysia where two Malaysian states namely Sabah and Sarawak are situated. In 2004, Polymerase Chain Reaction (PCR) was applied for diagnosing knowlesi malaria in the Kapit Division of Sarawak, Malaysia, so that human P. knowlesi infections could be detected correctly while blood film microscopy diagnosed incorrectly as Plasmodium malariae. This parasite is transmitted from simian hosts to humans via Anopheles vectors. Indonesia is the another country in South East Asia where knowlesi malaria is moderately prevalent. In the last decade, Sarawak and Sabah, the two states of east Malaysia became the target of P. knowlesi research due to prevalence of cases with occasional fatal infections. The host species of P. knowlesi are three macaque species namely Macaca fascicularis, Macaca nemestrina and Macaca leonina while the vector species are the Leucosphyrus Complex and the Dirus Complex of the Leucophyrus Group of Anopheles mosquitoes. Rapid diagnostic tests (RDT) are non-existent for knowlesi malaria although timely treatment is necessary for preventing complications, fatality and drug resistance. Development of RDT is essential in dealing with P. knowlesi infections in poor rural healthcare services. Genetic studies of the parasite on possibility of human-to-human transmission of P. knowlesi were recommended for further studies.